Complex proteomic analysis of furmint grapes infected with Botrytis cinerea - Szám, Dorottya; Pogány, Miklós; Hetesi, Zsolt; Takács, András Péter (GEORGIKON FOR AGRICULTURE, 2023)
Under optimal microclimatic and climatic conditions, as well as suitable soil characteristics in the Tokaj-Hegyalja wine region, Botrytis cinerea is of unique benefit in the production of Furmint aszú wine. The aim of our research was a complex proteomic study of grapes at different stages of ripening. We analysed berry samples collected from outside in which Furmint proteins were present, as well as intracellular and extracellular proteins of the fungus B. cinerea, which colonises the berries. The Kruskal–Wallis test revealed significant differences between samples at different stages of noble rot, both in terms of grape protein intensities and fungal protein intensities. In the case of fungal proteins, a significant difference between the intensity data of the samples was found when comparing fungi grown on grape berries with that of grown on agar medium. In all cases, the type of medium (artificial agar medium or grape berries) had a significant effect on the expression of fungal proteins, which was also true for the majority of grape proteins. The vast majority of the ANOVA and Kruskal–Wallis tests revealed significant differences for each protein, so that the stage of noble rot and the nature of the medium had a detectable effect on the majority of the proteins. The majority of grape proteins were produced in decreasing amounts as the grapes progressed through the senescence period, while the production of most of the fungal proteins increased over the same period.
Keywords: Botrytis cinerea; Furmint; grapevine; Tokaj; noble rot